Dimeria raviana (Poaceae: Panicoideae), a new species from Southern Western Ghats, India - S, Kiran Raj M; M, Sivadasan; Alfarhan, Ahmed H; Frederik Veldkamp, Jan Frederik (Phytotaxa, 2015)
Dimeria raviana, a new species of Poaceae from the Southern Western Ghats of Kerala, India is described and illustrated. It closely resembles D. fuscescens, but strikingly differs in having a flattened and winged raceme rachis of 1.0–1.25 mm in width with smooth margins.